Promoting the health of refugee women: a scoping literature review incorporating the social ecological model - Maren M. Hawkins; Marin E. Schmitt; Comfort Tosin Adebayo; Jennifer Weitzel; Oluwatoyin Olukotun; Anastassia M. Christensen; Ashley M. Ruiz; Kelsey Gilman; Kyla Quigley; Anne Dressel; Lucy Mkandawire-Valhmu (BMC, 2021)
Abstract The health of refugee women after settlement in a new country, can be adversely or positively affected by individual, interpersonal, community, and organizational factors. While much of the previous literature highlights these factors individually, there is a lack of comprehensive synthesis regarding how the factors interact to influence the health of refugee women. We conducted a thematic analysis in our literature review to elucidate how providers can work with refugee women to prevent adverse health outcomes and intervene at multiple levels to improve their health outcomes after resettlement. We reviewed peer-reviewed literature from 2009 to 2019 from Google Scholar, JSTOR, Global Health, PubMed, CINAHL, Sociological Abstracts, and Social Service Abstracts, and also used citation chaining, to identify relevant information pertaining to refugee women's health. The key terms used for our literature review were, health care, violence, social support, and mental health. In total, we included 52 articles, 3 books, and 8 other sources. We found that refugee women are vulnerable to violence during migration and typically have high rates of post-traumatic stress disorder. There were also concerns of secondary victimization by providers after resettlement. We also found that social support is an important factor for reducing isolation, and improving access to health care, as well as improving mental health outcomes. However, social support was often difficult to maintain, and was moderated by factors such as English language fluency. Health care was influenced by health literacy, cultural difference, communication concerns, and access issues. The findings suggest that at the individual and interpersonal levels there is a need to address language barriers, improve provider-patient communication, and provide appropriate medical and mental health screenings. At the organizational level, inter-organizational communication and awareness are vital. At the community level, providers can work with community leaders, to educate, create dialogue and collaboration, to help facilitate understanding and bolster community social support. Improved communication and knowledge about the unique needs and concerns of refugee women through an integrated, multi-system approach is necessary to improve their health outcomes.